ELASTODYNAMICAL MECHANISM OF RATE-DEPENDENT FRICTION - Pisarenko D. (My University, 2002)
We propose a model for the elastodynamical component of frictional interaction between two rough surfaces in contact. We consider the antiplane geometry and obtain the exact solution for stress within the contact of two asperities as a function of time, which includes elastic waves. The dynamical reaction of the elastic medium surrounding the asperity combined with a limited strength of the contact (characterized in the model by a modified Irwin's criterion), result in a velocity weakening friction. The origin of velocity weakening is explained by the form of the stress in the asperity as a function of time. The friction law is not imposed in the model but is obtained as the ensemble average of the frictional stress over a population of asperities. Numerical evaluation of such effective friction laws over four decades of variation of the slip velocity V leads to a 1/V-type velocity weakening friction.